Digital Marketing Melalui Pembuatan Web Profile dan Rebranding Kelompok Wanita Tani Melati Bojongmanggu - Nugroho, Heru; Widaningsih, Sri; Mandasari, Rizza Indah Mega; Umbara, Taufan; Susanty, Ade Irma; karlina, Lina (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2024)
Digital transformation is forcing global MSMEs to adopt technology, especially digital marketing. However, not all MSMEs are taking full advantage of it. In Indonesia, limited resources and low marketing skills challenge the growth of MSMEs. Digital marketing and market capability proved to influence performance, while rebranding became an important strategy. Digital marketing, through media such as the web and Instagram, has proven to be significant for MSME growth. The Bojongmanggu Women Farmers Group which has a programme in the cultivation and processing of sorghum plants into high economic value and healthy consumer products. The focus of this activity is the creation of a web profile, one of which contains a digital catalogue. In addition, facing the increasing intensity of competition through digital platforms, MSMEs are expected to expand their awareness in utilising Instagram as an effective tool to promote products. Although social media is effective, its management requires adequate time and understanding. Academic involvement in community service is key to accelerating the mastery of digital marketing concepts by MSMEs, supporting the sustainable growth of the sector.